Effect of Glyphosate Applications on Soil Properties - ศิริวงศ์, วภากร (KKU Science Journal, 2014)
Effects of glyphosate were found on properties of four soil types in a single and repeated glyphosate application. Soil pH was reduced in low clay and organic matter soils, but constant in high clay and organic matter soils after a single glyphosate application. The amount of available phosphorus was decreased in acid soils within three weeks after application and increased in the fourth week. Soil pH and zinc saturation percentage were the significant factors related to phosphorus reduction period whereas the initial content of phosphorus influenced the reduction magnitude. Four weeks after application, the amount of available phosphorus was increased in all soils that relevant to glyphosate dissipation half-life. The value of exchangeable potassium and magnesium was tend to reduce in all soils throughout the experiment, however the significant reduction was exhibited only in acid soils with low zinc saturation percentage. Long-term 4-repeating applications of glyphosate resulted in increasing of available phosphorus in the corresponding time to single application. The accumulation effect on phosphorus content was not found for each repeating applications. The reduction of glyphosate occurred naturally in the experiment. Relationship between soil glyphosate concentration and time after application was corresponded to the first order kinetic equation. DT50 was 16-33 days and was decreased in the repeated application.